Preconceptional Nutrition Knowledge Relationship and Energy Consumption Level with CED in Class XI of IPIEMS High School Surabaya - Azzizah Rahmawati Putri; Nur Hatijah; Nurul Hindaryani; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2023)
Chronic Energy Deficiency (CED) is a state of imbalance in energy and protein intake that lasts for a long time. One of the influencing factors is preconception nutritional knowledge and the level of energy consumption. The purpose of the study was to determine the relationship between preconception nutrition knowledge and the level of energy consumption with the incidence of CED in class XI SMA IPIEMS Surabaya. Research method, using analytical survey design with cross sectional. The sample of this study was 50 female students. The results of the study, the majority of female students were 17 years old and experienced CED. Have a deficient level of preconception nutritional knowledge and a severe deficit energy consumption level. There is a relationship between preconception nutrition knowledge with CED incidence (p = 0.005) and energy consumption level with CED incidence (p = 0.008) in class XI SMA IPIEMS Surabaya. The conclusion of this study is that there is a relationship between preconception nutrition knowledge, the level of energy consumption with the incidence of CED in class XI students of IPIEMS Surabaya High School, efforts that must be made are given counseling on proper nutrition from an early age to increase knowledge.